(untitled) (Journal of Hama University, 2019)
This study aims at comparing the depth of the articular fossa between Patients with Deep Bite and Normal occlusion. The samples consist of 26 Syrian adult, patients selected from the Department of Orthodontics, Faculty of Dentistry,Hama University. All subjects do not have any Temporal Mandibular Disorders ,and they have bilateral mastication pattern.The subjects are divided into two groups: Control group: consist of 13 subjects with mean age (23.7) with the following criteria: incisor overlapping (5-25)% ,skeletal and dental Class I (ANB = 2 – 4), natural growth pattern (FMA= 22+2( Group 2: deep bite/ class I malocclusion: consist of 13 subjects with mean age (28.6) with the following criteria: incisor overlapping >40%.skeletal and dental Class I (ANB = 2–4), horizontal growth pattern (FMA< 22+2). Then computed tomography images were obtained by Cone Beam Computed Tomogram technique. to achieve the depth of the articular fossa, this measurements were conducted by the 17 MIMICS® program. This study shows that the depth of the articular fossa is larger in the deep bite sample in comparasion with the normal occlusion sample.